A Prospective-Randomized Study: The Impact of Four Different Caries Removal Method on Pain and Clinical Evaluations - Aydemir, Merve; Bağlar, Serdar (UI Scholars Hub, 2023)
Objective: There are many different methods for removing caries. In this study, to evaluate four caries removal methods in terms of patient comfort and to evaluate the clinical success of restorations according to modified-USPHS criteria. Methods: In 31 patients with at least 4 Class II caries in their posterior teeth, 4 teeth were randomly divided into four groups and 4 different methods (conventional method, Carisolv, Papacarie, Er-Cr:YSGG Laser) were used for caries removal. Pain formation during caries removal was determined by FACE Pain Scale questionnaire. The restorations were controlled with Modified-USPHS criteria in 3-6-12 months period. Mann-Whitney U test for two-group comparisons, Kruskal Wallis H test for comparison of three or more groups, Wilcoxon Sign test was used to examine the changes according to time (p < 0.05). Results: A significant difference was found between conventional methods and alternative methods in terms of pain tolerance. In the 1-year clinical evaluation of the restorations, there was a significant decrease in the postoperative sensitivity in all groups. A significant difference was detected in Carisolv and laser groups between 6-months and 12-months for marginal coloration. A significant difference was found between the conventional and laser groups between 6-months and 12-months in terms of color match. Conclusion: The success of restorations, efficacy and efficiency of the methods used in the evaluation of all groups were found to be successful. In terms of patient comfort, all alternative methods gave positive results.